Does complete plastid genome sequencing improve species discrimination and phylogenetic resolution in Araucaria?. (15th February 2015) - Ruhsam, Markus; Rai, Hardeep S.; Mathews, Sarah; Ross, T. Gregory; Graham, Sean W.; Raubeson, Linda A.; Mei, Wenbin; Thomas, Philip I.; Gardner, Martin F.; Ennos, Richard A.; Hollingsworth, Peter M.
Abstract Obtaining accurate phylogenies and effective species discrimination using a small standardized set of plastid genes is challenging in evolutionarily young lineages. Complete plastid genome sequencing offers an increasingly easy‐to‐access source of characters that helps address this. The usefulness of this approach, however, depends on the extent to which plastid haplotypes track morphological species boundaries. We have tested the power of complete plastid genomes to discriminate among multiple accessions of 11 of 13 New Caledonian Araucaria species, an evolutionarily young lineage where the standard DNA barcoding approach has so far failed and phylogenetic relationships have remained elusive. Additionally, 11 nuclear gene regions were Sanger sequenced for all accessions to ascertain the success of species discrimination using a moderate number of nuclear genes. Overall, fewer than half of the New Caledonian Araucaria species with multiple accessions were monophyletic in the plastid or nuclear trees. However, the plastid data retrieved a phylogeny with a higher resolution compared to any previously published tree of this clade and supported the monophyly of about twice as many species and nodes compared to the nuclear data set. Modest gains in discrimination thus are possible, but using complete plastid genomes or a small number of nuclear genes in DNA barcoding may not substantially raise species discriminatory power in many evolutionarily young lineages. The big challenge therefore remains to develop techniques that allow routine access to large numbers of nuclear markers scaleable to thousands of individuals from phylogenetically disparate sample sets.